Hell's islands : the untold story of Guadalcanal - Jersey, Stanley Coleman, 1921- (Texas A & M University military history series, 2008)
Presents battlefield accounts and first-person narratives from over 200 Allied and Japanese veterans of the battle on Guadalcanal Island between August 1942 and February 1943.